KOMUNIKASI ANTI KEKERASAN: Membangun Budaya Damai dalam Perspektif Etika Komunikasi Islam - Bahtar, Bahtar (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2013)
Communication with good language as part of a system of Islamic teaching that can create harmony of human life. However, in public life, we often find motifs such violence; rough character, emotional, anarchist, and brutal act with say tabok, jitak, sikat and others. Therefore, in the area of non-violent communication, communicators as preachers are required to avoid words thay may appear to conflict for the whole society and change to the polite language of communication, straightforward, wise, and accomodatong that underestimate another person or group f social interaction a day-to-day that all forms of violence do not appear in the public.